Airway management during in-hospital cardiac arrest: An international, multicentre, retrospective, observational cohort study. (August 2020) - Penketh, J.A.; Nolan, J.P.; Skrifvars, M.B.; Rylander, C.; Frenell, I.; Tirkkonen, J.; Reynolds, E.C.; Parr, M.J.A.; Aneman, A.
Abstract: Aim: To determine the type of airway devices used during in-hospital cardiac arrest (IHCA) resuscitation attempts. Methods: International multicentre retrospective observational study of in-patients aged over 18 years who received chest compressions for cardiac arrest from April 2016 to September 2018. Patients were identified from resuscitation registries and rapid response system databases. Data were collected through review of resuscitation records and hospital notes. Airway devices used during cardiac arrest were recorded as basic (adjuncts or bag–mask), or advanced, including supraglottic airway devices, tracheal tubes or tracheostomies. Descriptive statistics and multivariable regression modelling were used for data analysis. Results: The final analysis included 598 patients. No airway management occurred in 36 (6%), basic airway device use occurred at any time in 562 (94%), basic airway device use without an advanced airway device in 182 (30%), tracheal intubation in 301 (50%), supraglottic airway in 102 (17%), and tracheostomy in 1 (0.2%). There was significant variation in airway device use between centres. The intubation rate ranged between 21% and 90% while supraglottic airway use varied between 1% and 45%. The choice of tracheal intubation vs. supraglottic airway as the second advanced airway device was not associated with immediate survival from the resuscitation attempt (odds ratio 0.81; 95% confidence interval 0.35–1.8). Conclusion: There is wide variation in airway device use during resuscitation after IHCA. Only half of patients are intubated before return of spontaneous circulation and many are managed without an advanced airway. Further investigation is needed to determine optimal airway device management strategies during resuscitation following IHCA.